Review Hepatoprotektor Rosela (Hibiscus sabdariffa): Aktivitas, Mekanisme Aksi dan Toksisitas: Review of Hepatoprotector of Rosela (Hibiscus sabdariffa) : Activity, Mechanism of Action and Toxicity - Steffi Liem; Jutti Levita (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
Liver cirrhosis has become the international health problem that causes significant mortality. Handling using herbs from various countries has been done, one of them by consuming roselle (Hibiscus sabdariffa) calyx extract. H. sabdariffa contains anthocyanins, flavonoids, tannins, and ascorbic acid that function as hepatoprotector. H. sabdariffacalyx extract may inhibit the increasing of various clinical parameters, such as ALT, AST, ALP, and LDH in various inducer types, ie acetaminophen, CCl4, CdCl2, DNPH, and TAA. The mechanism of action of H. sabdariffacalyx extract are as an antioxidant, inhibition of cytochrome enzyme, induction of phase II metabolism enzymes, increase cell viability percentage, increase CAT, GSH and decrease protein expression of pJNK, tBid and Bax. However, the consumption of H. sabdariffacalyx extract may also cause acute, subchronic, and chronic toxicity depending on the given dose.